Answer:
[tex] -3 +2y \leq 4x[/tex]
[tex] 2y \leq 4x+3[/tex]
[tex] y \leq 2x + \frac{3}{2}[/tex]
And that's different from the claim of the student that:
[tex] y \geq 2x +\frac{3}{2}[/tex]
The error of the student is that he/she changes the sign of the inequality from [tex] \leq[/tex] to [tex]\geq[/tex] and that's not possible since we don't multiply both sides of the equation by -1
Step-by-step explanation:
For this case we have the following inequality:
[tex] -3 +2y \leq 4x[/tex]
We want to rewrite the last expression with y in the left and x in the right so we can begin adding 3 in both sides of the inequality and we got:
[tex] 2y \leq 4x+3[/tex]
Now we can divide both sides of the inequality by 2 and we got:
[tex] y \leq 2x + \frac{3}{2}[/tex]
And that's different from the claim of the student that:
[tex] y \geq 2x +\frac{3}{2}[/tex]
The error of the student is that he/she changes the sign of the inequality from [tex] \leq[/tex] to [tex]\geq[/tex] and that's not possible since we don't multiply both sides of the equation by -1